Societal change and language history in Cernvantes' entremeses: The status of the Golden Age vos. - KING, JEREMY (Cervantes)
The article analyzes the entremeses found in the eight comedies of Miguel de Cervantes. It examines the use of pronominal forms of address provided in his works and analyzes the pragmatic and sociolinguistic motivations in using each address pronoun within the context of the Spanish Golden Age. Other similar investigations are cited in the article to compare its findings and their implications in studying the sociological aspects of the Spanish Renaissance era.